Deterministic Progenitor Behavior and Unitary Production of Neurons in the Neocortex - Gao, Peng; Postiglione, Maria Pia; Krieger, Teresa G.; Hernandez, Luisirene; Wang, Chao; Han, Zhi; Streicher, Carmen; Papusheva, Ekaterina; Insolera, Ryan; Chugh, Kritika; Kodish, Oren; Huang, Kun; et al. (Cell, 2014)
Radial glial progenitors (RGPs) are responsible for producing nearly all neocortical neurons. To gain insight into the patterns of RGP division and neuron production, we quantitatively analyzed excitatory neuron genesis in the mouse neocortex using Mosaic Analysis with Double Markers, which provides single-cell resolution of progenitor division patterns and potential in vivo. We found that RGPs progress through a coherent program in which their proliferative potential diminishes in a predictable manner. Upon entry into the neurogenic phase, individual RGPs produce ?8-9 neurons distributed in both deep and superficial layers, indicating a unitary output in neuronal production. Removal of OTX1, a transcription factor transiently expressed in RGPs, results in both deep- and superficial-layer neuron loss and a reduction in neuronal unit size. Moreover, ?1/6 of neurogenic RGPs proceed to produce glia. These results suggest that progenitor behavior and histogenesis in the mammalian neocortex conform to a remarkably orderly and deterministic program.